Bilateral Intracranial Beta Activity During Forced and Spontaneous Movements in a 6-OHDA Hemi-PD Rat Model - Mottaghi, Soheil; Kohl, Sandra; Biemann, Dirk; Liebana, Samuel; Montaño Crespo, Ruth Eneida; Buchholz, Oliver; Wilson, Mareike; Klaus, Carolin; Uchenik, Michelle; Münkel, Christian; Schmidt, Robert; Hofmann, Ulrich G. (Frontiers in Neuroscience, 2021)
Cortico-basal ganglia beta oscillations (13-30Hz) are assumed to be involved in motor impairments in Parkinson’s Disease (PD), especially in bradykinesia and rigidity. Various studies have utilized the unilateral 6-OHDA rat PD model to further investigate PD and test novel treatments. However, a detailed behavioral and electrophysiological characterization of the model, including analyses of popular PD treatments such as DBS, has not been documented in the literature. We hence challenged the 6-OHDA rat PD model with a series of experiments (i.e. cylinder test, open field test and rotarod test) aimed at assessing the motor impairments, analyzing the effects of Deep Brain Stimulation (DBS), and identifying under which conditions excessive beta oscillations occur. We found that hemi-PD rats presented an impaired performance in all experiments compared to the sham group, and DBS could improve their overall performance. Across all the experiments and behaviors, the power in the high beta band was observed to be an important biomarker for PD as it showed differences between healthy and lesioned hemispheres and between PD and sham rats. This all shows that the 6-OHDA PD model accurately represents many of the motor and electrophysiological symptoms of PD and makes it a useful tool for the pre-clinical testing of new treatments when low  (13-21Hz) and high  (21-30Hz) frequency bands are considered separately.